Cuneiform Texts. Old Babylonian Contracts and Juridical Texts - van Dijk, Jan (1967)
Published by the Directorate General of Antiquities, Baghdad; IM 10861 = no. 45, pl. XLV: MA marriage contract; in Arabic.